Perception of HIV/AIDS Patients with Pulmonary TB on Family Support in Taking OAT ARV Medications - In Handani, Aprida Luk Luk (Health Gate, 2024)
abstractFamily support in reminding sufferers to take ARV medication can influence their medication compliance. Sufferers can despair if there is no family support and this can have bad consequences. The aim of the research was to explore the perceptions of HIV/AIDS sufferers with pulmonary TB regarding family support in taking ARV oat medication. The research design is qualitative using a phenomenological study. Samples based on criteria for treatment, living with family and willing to be respondents. The research sample used a total population of 3 respondents. The results of the interviews showed support for the assessment, all respondents felt that they were well received by their families and that the family had an important role in getting well, thereby motivating them to receive regular treatment. Instrumental support: All respondents said that medical needs were met by the family and it was not uncommon for sufferers to be invited to go on recreation. Informational support, some families do not know enough about providing health information and the family has explained the importance of taking medication. Emotional support, respondents said they felt disappointed and a burden when the family understood about illnesses that could be contagious. Overall family support in assessment, instrumental, informational and emotional is good but can be improved regarding providing health information and maintaining motivation to take medication.